Potential of natural astaxanthin in alleviating the risk of cytokine storm in COVID-19 (2020)
Host excessive inflammatory immune response to SARS-CoV-2 infection is thought to underpin the pathogenesis of COVID-19 associated severe pneumonitis and acute lung injury (ALI) or acute respiratory distress syndrome (ARDS). Once an immunological complication like cytokine storm occurs, anti-viral based monotherapy alone is not enough. Additional anti-inflammatory treatment is recommended. It must be noted that anti-inflammatory drugs such as JAK inhibitors, IL-6 inhibitors, TNF-α inhibitors, colchicine, etc., have been either suggested or are under trials for managing cytokine storm in COVID-19 infections. Natural astaxanthin (ASX) has a clinically proven safety profile and has antioxidant, anti-inflammatory, and immunomodulatory properties. There is evidence from preclinical studies that supports its preventive actions against ALI/ARDS. Moreover, ASX has a potent PPARs activity. Therefore, it is plausible to speculate that ASX could be considered as a potential adjunctive supplement. Here, we summarize the mounting evidence where ASX is shown to exert protective effect by regulating the expression of pro-inflammatory factors IL-1β, IL-6, IL-8 and TNF-α. We present reports where ASX is shown to prevent against oxidative damage and attenuate exacerbation of the inflammatory responses by regulating signaling pathways like NF-ĸB, NLRP3 and JAK/STAT. These evidences provide a rationale for considering natural astaxanthin as a therapeutic agent against inflammatory cytokine storm and associated risks in COVID-19 infection and this suggestion requires further validation with clinical studies.